Potensi Ekstrak Kunyit sebagai Inhibitor Korosi Ramah Lingkungan untuk Baja Karbon Rendah - Sajida, Gita Nur; Krista, Gustin Mustika; Sari, Hermin Kartika; Taufiqurohim, Teguh; Ferawati, Yohana Fransiska; Sihombing, Rony Pasonang (Jurnal Teknologi, 2025)
Corrosion is a significant metal degradation problem causing substantial economic losses, particularly in the oil and gas industry. Traditional chromate-based inhibitors are toxic, spurring the search for eco-friendly alternatives. This article explores the potential of Curcuma longa (turmeric) extract as a natural corrosion inhibitor for low-carbon steel plates in acidic and basic media. This study tests turmeric extract on low-carbon steel plates in HCl and NaOH media using immersion test (weight loss). The active compound curcumin in turmeric extract effectively inhibits corrosion. Its effectiveness is highly dependent on the solvent type and concentration; 0.25% NaOH yields up to ~87% effectiveness at 1000 ppm turmeric concentration, with a corrosion rate of 0.697 mdd, significantly outperforming 0.25% HCl which only reaches ~22% at similar concentrations with a corrosion rate of 133.99 mdd. Increasing NaOH concentration to 0.50% drastically enhances initial effectiveness, reaching ~63% at 100 ppm, and 90% at 400 ppm, with the corrosion rate dropping to 0.668 mdd.